Anatomical Adaptation of Schumannianthus dichotomus (Roxb.) Gagnep.: Marantaceae in Dry and Wet Conditions - Thanomchat, Piyanan; Paopun, Yupadee; Kermanee, Prasart (Science Essence Journal, 2020)
บทคัดย่อ คล้าน้ำ (Schumannianthus dichotomus (Roxb.) Gagnep.) เป็นพืชใบเลี้ยงเดี่ยวจัดอยู่ในวงศ์ Marantaceae ในธรรมชาติคล้าสามารถเจริญได้ทั้งในน้ำและที่แห้งแล้ง จึงได้ทำการศึกษาวิเคราะห์ลักษณะทางกายวิภาคศาสตร์และการปรับตัวให้เจริญเติบโตได้ในทั้งสองสภาพดังกล่าว โดยเก็บตัวอย่างราก ลำต้นใต้ดิน ลำต้นเหนือดิน และใบมาผลิตเป็นสไลด์ถาวรตามกรรมวิธีพาราฟฟิน การแช่ยุ่ยเนื้อเยื่อ และการฟอกใสตัวอย่าง จากการศึกษาพบกายวิภาคศาสตร์ของคล้าน้ำมีลักษณะที่ผสมผสานกันระหว่างพืชน้ำคือรากมีช่องอากาศใหญ่ ลำต้นใต้ดินมีชั้นเอนโดเดอร์มิส ลำต้นเหนือดินมีเนื้อเยื่อแอเรงคิมาจำนวนมาก ผิวใบมีชั้นคิวติเคิลบาง และลักษณะของพืชแล้งคือลำต้นเหนือดินมีคิวติเคิลหนา มีเซลล์ไฟเบอร์มาก ในใบมีเนื้อเยื่อไฮโปเดอร์มิสที่ทำหน้าที่เก็บน้ำ จากการที่มีลักษณะดังกล่าวจึงทำให้คล้าน้ำสามารถเจริญได้ทั้งในน้ำและบนบก ABSTRACT Schumannianthus dichotomus (Roxb.) Gagnep.is a monocotyledonous plant in the family Marantaceae. According to the species can naturally grows in both wet and dry conditions, the anatomical character was investigated and analysed. Roots, rhizomes, aerial stems and leaves were prepared into permanent slides using a paraffin method, tissue maceration and tissue clearing techniques. The results revealed that the anatomical character of Schumannianthus dichotomusconsists of both hydrophytic and xerophytic characters. The hydrophytic characters are the presence of large lacunae in root, endodermis in rhizome, aerenchyma in aerial stem, and thin layer of cuticle on the leaf surface. The xerophytic characters are thick cuticular layer, abundant fiber cells in aerial stem, and the presence of hypodermis, a water storage tissue in leaf. Consequently, Schumannianthus dichotomus can normally grow in wet and dry conditions.